Notes on the Development of the Slovenian Ethical Recommendations for Decision-Making on Treatment and Palliative Care of Patients at the End of Life in Intensive Care Medicine. (August 2018) - Grosek, Stefan; Orazem, Miha; Groselj, Urh
Abstract : Objectives: To describe the process of development of "Slovenian Ethical Recommendations for Decision-Making on Treatment and Palliative Care of Patients at the End of Life in Intensive Care Medicine" and its final outcomes. Data Sources: Personal experience and reflection, complemented by published data. Study Selection: Not applicable. Data Extraction: Not applicable. Data Synthesis: Narrative, experiential reflection, literature review. Conclusions: Slovenian ethical recommendations bring a small piece to a long tradition of ethical practice in a small European country. Despite the availability of informative international guiding documents on the issue, there are several specific good reasons for a small country or a region to develop its own unique guidelines (i.e., lack of local directives and legislation, unique cultural and political situation, need for development of professional expertise and terminology, and to educate healthcare providers). The authors strongly believe that our recommendations positively impact practice and will support best possible integrated palliative and end-of-life quality care with the ICU.